2008
DOI: 10.1096/fj.08-111872
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin‐11 knockout mice and polycystic kidney disease animals share a common mechanism of cyst formation

Abstract: Aquaporin-11 (AQP11), a new member of the aquaporin family, is localized in the endoplasmic reticulum (ER). Aqp11(-/-) mice neonatally suffer from polycystic kidneys derived from the proximal tubule. Its onset is proceeded by the vacuolization of ER. However, the mechanism for the formation of vacuoles and cysts remains to be clarified. Here, we show that Aqp11(-/-) mice and polycystic kidney disease (PKD) animals share a common pathogenic mechanism of cyst formation. We performed microarray analyses and histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 53 publications
6
35
0
Order By: Relevance
“…23 These data indicated that aberrantly glycosylated PC-1 might fail to enter the degradation pathway in AQP11(2/2) kidney because of the inability of PC-1 to exit the ER in the AQP11(2/2) kidney. Additional investigation will be required to clarify this issue.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…23 These data indicated that aberrantly glycosylated PC-1 might fail to enter the degradation pathway in AQP11(2/2) kidney because of the inability of PC-1 to exit the ER in the AQP11(2/2) kidney. Additional investigation will be required to clarify this issue.…”
Section: Discussionmentioning
confidence: 85%
“…4 In addition, increased ER stress response and oxidative stress in AQP11(2/2) mice were recently reported. [23][24][25] Therefore, AQP11 may play an important role in the homeostasis of the ER, and the absence of AQP11 could lead to ER dysfunction. However, to the best of our knowledge, there are no reports showing that renal cystogenesis is caused by nonspecific disruption of ER function.…”
Section: Discussionmentioning
confidence: 99%
“…However, several recent studies seem to have hinted at the mechanisms underlying the body axis curvature induced by deficiency of AQP11 in zebrafish. Using microarray analyses, Okada et al (33) have shown that the kidneys of 1-week-old AQP11-null and wild-type mice exhibit a significant change in the expression of three genes (Myc, Egfr, and Egf) involved in cell proliferation and three genes associated with remodeling of the extracellular matrix (Mmp12, Timp1, and Tgfb1). Expression of Myc, Egfr, Mmp12, Timp1, and Tgfb1 was found to be up-regulated in Aqp11 Ϫ/Ϫ mice, whereas Egf was down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it is likely that AQPs other than AQP8 play complementary, tissue-and context-specific roles with regard to H 2 O 2 transport at the ER. One obvious candidate is AQP11, the subcellular localization of which is strongly shifted to the ER [45,46]. AQP11 loss-of-function causes destructive symptoms of ER stress, which mainly manifest in the proximal tubular epithelial cells of the kidney [45][46][47] but also in other organs such as the liver [48].…”
Section: Aquaporins Regulate the Permeability Of The Er Membrane To Hmentioning
confidence: 99%
“…One obvious candidate is AQP11, the subcellular localization of which is strongly shifted to the ER [45,46]. AQP11 loss-of-function causes destructive symptoms of ER stress, which mainly manifest in the proximal tubular epithelial cells of the kidney [45][46][47] but also in other organs such as the liver [48]. In addition to the tissue-specific expression level of ER AQPs, the H 2 O 2 permeability of the ER membrane is likely regulated by post-translational modifications.…”
Section: Aquaporins Regulate the Permeability Of The Er Membrane To Hmentioning
confidence: 99%